1984
DOI: 10.2307/1143210
|View full text |Cite
|
Sign up to set email alerts
|

Toward Criminal Jury Instructions That Jurors Can Understand

Abstract: in collecting data reported herein. We also acknowledge the help of Jane Goodman in providing psycholinguistic analyses of protocol data reported herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 0 publications
1
58
0
Order By: Relevance
“…However, no significant differences were found for evidence, F (3, subscale 1 (authoritarianism) of the RLAQ were less likely to comprehend the legal terms of reasonable doubt and evidence (see Table 3). However, no significant differences were found for murder aforethought, F (3,308 …”
Section: Juror Instructions and Legal System Attitudesmentioning
confidence: 80%
“…However, no significant differences were found for evidence, F (3, subscale 1 (authoritarianism) of the RLAQ were less likely to comprehend the legal terms of reasonable doubt and evidence (see Table 3). However, no significant differences were found for murder aforethought, F (3,308 …”
Section: Juror Instructions and Legal System Attitudesmentioning
confidence: 80%
“…Finally, we measured comprehension in the abstract, that is, without involving any discussion or instruction from a lawyer who, one would hope, could explain the concepts in ways that the client could understand. In their study of the comprehensibility of jury instructions, Severance, Greene, and Loftus (1984) showed that jurors' understanding was enhanced when jury instructions were simplified and when individual jurors had the opportunity to deliberate as a jury.…”
Section: Discussionmentioning
confidence: 99%
“…Pattern instructions are diffi cult to understand because they tend to be quite lengthy and rely heavily on legal jargon (Severance, Greene, & Loftus, 1984 ). Legal professionals who write instructions might also be unaware of research on psycholinguistics, which suggests what factors might infl uence reading or auditory comprehension (e.g., Charrow & Charrow, 1979 ).…”
Section: The Legal Perspectivementioning
confidence: 99%